Novel simulation-based education used for Domestic Abuse Screening for Emergency Department Healthcare Professionals: Normalizing Assessment at Triage / Formation novatrice basée sur la simulation pour le dépistage de la violence domestique auprès des professionnels de la santé au service des urgences : normaliser l’évaluation au triage - Peta, Dawn; Mundell, Annamaria; Dolan, Sara; Laberge, Jason; Kaba, Alyshah (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Purpose: Rural emergency department healthcare professionals are well-positioned to serve as a resource to domestic violence victims but may lack the necessary training to effectively screen for and respond to domestic violence victims. A novel, low fidelity simulation-based education provided an opportunity to increase healthcare professionals’ readiness to screen for domestic violence.Methods: We facilitated 14 simulations with 181 participants at eight rural sites between September 2022 and June 2023. A multi-method program evaluation was used to assess the impact of the simulation-based education on participants' readiness to screen for domestic violence and their clinical practice. Participants of the simulation were invited to complete a pre and post-simulation survey regarding their experience and perceptions related to screening for domestic violence. Participants were invited to participate in follow-up semi-structured interviews to discuss how simulation-based education has influenced their practice three to nine months following the simulation.Results: Prior to the simulation-based education participants reported several barriers to screening for domestic violence and a lack of training. Following simulation-based education, a statistically significant increase in readiness to screen for domestic violence was observed, t (102) = 19.43, p <.001, d = 1.91 between the pre- and post-simulation survey scores (n = 103). Through semi-structured interviews (n = 6), two themes were identified: (a) influence on education and (b) the power of simulation-based education.Conclusions: Simulation-based education is an effective education modality to enhance healthcare professionals’ readiness to screen patients for domestic violence and may positively influence their practice through increased awareness and more consistent screening.